Developmental capacity of goat oocytes collected from 5°C preserved ovaries - Ita Djuwita (Hemera Zoa, 2010)
Research has been conducted to study the effect of ovaries preservation at 5°C on the oocytes development capacity i.e the capacity of oocytes to undergo in vitro maturation (IVF), in vitro fertilization (IVF) and in vitro embryo development. Goat ovaries were abtained from slaughterhouse in saline solution containing 0.1% Bovine Serum Albumine (BSA) and antibiotic and kept at 5°C for 3 and 12 hours. As control, untreated ovaries were kept for 3 hours at 30-35°C, the temperature usually used for ovaries transportation. The oocytes were aspirated from follicles with 2-5 mm in diameter using 20G needle connected to a 5 ml syringe containing modified phosphate buffered saline (mPBS). The aspirated oocytes were incubated in 100 µl  micro drops of tissue culture medium -199 (TCM-199) supplemented with 10% newborn calf serum (NBCS), 0.01 mg/ml follicle stimulating hormore (FSH) and 50  µg/ml   gentamycine sulphate for 24 hours at 38.5 °C in 5% CO2 incubator. In vitro fertilization (IVF) was done in CO2 incubator at 38.5 °C for 18 hours using fresh semen. Inseminated by their nuclear status after aceto-orcein staining. The results showed that the avarage number of morphological normal oocytes collected from 5 °C  preserved  ovaries were significantly lower than from the untreated control ovaries. After 24 h incubation the percentage of matured oocytes from the 3 ang 12 h preserved ovaries were 85.3± 2.8% and 75.5±  2.2%, respectively (P